Performance analysis of voltage source converter based high voltage direct current line under small control perturbations - Reem Ahmed Mostafa; Adel Emary Salem; Ahmed Sayed Abdelhamid; Mohamed EL-Shimy Mahmoud Bekhet (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
High voltage direct current (HVDC) systems provide important advantages; among them the ability to transmit enormous amounts of electrical power over great distances at low cost. As a result, planners of power systems consider it as a viable choice   for power transmission and interconnection of asynchronous networks. Depending on HVDC grids, continental/super grids have been recently constructed to promote global economic development. The study described in the paper focuses on the behavior of  a voltage sourced converter (VSC) based HVDC  transmission system comprising three arms-neutral point  clamped (NPC) converters interconnecting two asynchronous alternating current (AC)networks. In addition, the system components, and the vector control strategy of active/reactive powers and direct current (DC)bus voltage are simulated in MATLAB/Simulink under varying situations by adjusting the  controller’s  settings.  The study records and analyzes AC/DC voltages and active/reactive powers at two converter stations undervarying power and voltage conditions. The results of the study provide key performance indicators, such as settling time (tsett), steady state error (SSE), overshot/undershoot (OS%/US%), and correlation factor (CF), which demonstrate the robustness of thesystem’s control.